Tingkat kerusakan dan serangan hama buah lada, Dasynus piperis china pada pertanaman lada di bangka - I Wayan Laba; D. Kilin; Iwa Mara Trisawa (Jurnal Entomologi Indonesia, 2004)
Berry sucker insect pest, Dasynus piperis china (coreidae; Hemiptera) is one of the major insect pest on pepper. D. piperis to attack fruit of pepper with suck of fruit liquid and the final effect is empty to fruit and damaged. To find out of the level of damage and destruction caused by D. piperis have been done at 6 districts of Bangka Island namely Mendo Barat, Sungai Selan, Sungai Liat, Belinyu, Koba and Toboali since January to December 2002. For each district were observed 5 farmers field of estate crops. Every farmer field were observed tens plant of pepper in connection with fluctuation population and level of fruit damage. The observation have been done on the flower season of pepper, after flower season and after harvest. The result showed that fluctuation population and infested level of D. piperis at each observation almost the same, while among district were variated. The highest infestation was found in Sungai Selan, followed by Belinyu, and Mendo Barat namely 36.82;32.03 and 29.48 % respectively. The infestation level on Sungai Liat, Toboali and Koba were low namely 14;79.58 and 20.98 % respectively. The level of damage in Mendo Barat was highest than an other location namely 8.66; 8.07; 6.67; 5.71;4.89 and 3.09 % in Mendo Barat, Sungai Selan, Belinyu, Koba, Toboali and Sungai Liat respectively.